Effects of low-temperature stress during rice heading stage on carbon and nitrogen allocation in paddy eco-system of northeastern China - Sun, Tao; Ruan, Junmei; Cao, Tiehua; Yao, Li; Zhao, Zichao; Zhang, Jun; Li, Jiarui; Deng, Aixing; Chen, Haotian; Gao, Xinhao; Song, Zhenwei (Frontiers in Plant Science, 2025)
IntroductionIn high-latitude area, climate change has brought about recurrent chilling stress that adversely impacts the sustainable production of rice and alters the distribution of carbon (C) and nitrogen (N) in paddy ecosystems. A comprehensive understanding of how the paddy ecosystem’s C and N allocation responds to low-temperature stress during critical growth stages remains elusive.MethodsA rice pot experiment of two varieties combined with 13C and 15N isotope labelling method was conducted to evaluate how low temperature stress at heading stage affects rice yield, and above- and belowground C and N partitioning.Results and DiscussionLow-temperature stress significantly reduced rice grain yield of JN809 (sensitive to low-temperature stress) and J88 (tolerant to low-temperature stress) varieties by 27.6% and 21.4%, respectively, This stress tendency increased C and N accumulation in rice stems and leaves, while concurrently decreasing C and N accumulation in panicles. Specifically, under low-temperature stress, the 13C isotope content in stems and leaves was found to be 14.0% and 19.0% higher than in the control treatment, while the 13C and 15N isotope contents in their panicles were 29.3% and 22.5% lower, respectively. The low-temperature tolerant variety (J88) demonstrated a reduced effect of low-temperature stress on rice yield and C, N allocation due to efficient resource reallocation and stress tolerance mechanisms. The findings of this study provide a foundation for developing rice breeding and cultivation techniques that can enhance rice resilience and adaptability to climate change. Additionally, it informs strategies to optimize C and N sequestration practices in rice fields, ensuring high yields and efficient resource utilization.